Searching for correlations in simultaneous X-ray and UV emission in the narrow-line Seyfert 1 galaxy 1H 0707–495 - Robertson, D. R. S.; Gallo, L. C.; Zoghbi, A.; Fabian, A. C. (Monthly notices of the Royal Astronomical Society, 2015)
We examine simultaneous X-ray and UV light curves from multi-epoch 8 d XMM–Newton observations of the narrow line Seyfert 1 galaxy 1H 0707–495. The simultaneous observations reveal that both X-ray and UV emission are variable and that the amplitude of the X-ray variations is significantly greater than that of the UV variations in both epochs. Using a discrete correlation function the X-ray and UV light curves were examined for correlation on time-scales up to 7 d. Low-significance (∼95 per cent confidence) correlations with the UV leading the X-ray variations are observed. The lack of a significant correlation between the UV and X-ray bands seems consistent with the X-ray source being centrally compact and dominated by light bending close to the black hole. In addition, multiband X-ray light curves were examined for correlations on similar time-scales. Highly significant (>99.9 per cent confidence) correlations were observed at zero lag consistent with previous studies of this active galactic nucleus.